Dampak Pendidikan Agama Islam (PAI) terhadap Pengembangan Moral pada Siswa Muslim - Husni, Hafizul (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2024)
This article discusses the impact of Islamic education on the moral development of Muslim students. The aim of Islamic education is to bring students closer to God and enlighten humanity. To form good morals in students' lives, appropriate strategies are needed in implementing Islamic education. The problem formulation in this research is the impact of Islamic religious education on the moral development of Muslim students. The aim is to determine the impact of Islamic religious education on the moral development of Muslim students. This research includes quantitative research. The approach used is descriptive quantitative. Data was obtained by distributing a questionnaire to students with a total of 10 questions. The data analysis technique uses the percentage of answers from the questionnaire. The population and sample in this study amounted to 74 students. The research results show that the impact of PAI on the moral development of Muslim students is in the "high" category. This can be proven from the research results of the students' total score of 76.2%.